2006
DOI: 10.1002/ejoc.200500944
|View full text |Cite
|
Sign up to set email alerts
|

Functionalized 1‐Alkoxy‐1,3‐dienes: Their Preparation and Applications in Synthetic Organic Chemistry

Abstract: The reaction of various α,β‐unsaturated acetals with two equivalents of the Schlosser reagent LIC‐KOR [equimolar mixture of BuLi (LIC), and tBuOK (KOR)] gives 1‐metalated (1E)‐1‐alkoxy‐1,3‐dienes. These products can be transformed into trienic derivatives that are apt to participate in intramolecular Diels–Alder (IMDA) cycloaddition reactions, and can also be transformed into bifunctional (γ‐halo‐α‐carbonyl) reagents. Moreover, the metalated dienes can be readily functionalized with suitable electrophiles to a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(20 citation statements)
references
References 91 publications
0
17
0
Order By: Relevance
“…The hetero Diels-Alder reaction (HDA) has been amply used in the de novo synthesis of hexoses, and in many those instances 2,3-unsaturated derivatives have been key intermediates in these protocols [27,28,29]. Pioneering work by Danishefsky’s group had shown that hexoses could be accessed by Lewis acid-catalyzed HDA reaction of alkylated siloxy dienes with aldehydes via the intermediacy of labile 3- O -silyl-2,3-unsaturated glycoside adducts [30,31].…”
Section: Synthetic Routes To Hex-2-enopyranosidesmentioning
confidence: 99%
“…The hetero Diels-Alder reaction (HDA) has been amply used in the de novo synthesis of hexoses, and in many those instances 2,3-unsaturated derivatives have been key intermediates in these protocols [27,28,29]. Pioneering work by Danishefsky’s group had shown that hexoses could be accessed by Lewis acid-catalyzed HDA reaction of alkylated siloxy dienes with aldehydes via the intermediacy of labile 3- O -silyl-2,3-unsaturated glycoside adducts [30,31].…”
Section: Synthetic Routes To Hex-2-enopyranosidesmentioning
confidence: 99%
“…As a consequence, substantial efforts have been made over the years by synthetic organic chemists in order to design and develop methods allowing efficient access to a variety of functionalized allenes, 4 alkynes 5 and 1,3-dienes. 6 Meanwhile, the widespread use of uorinated, especially triuoromethylated, compounds in pharmaceutical chemistry, agrochemistry 7 and materials science 8 has attracted considerable interest in development of various synthetic methodologies for synthesis of these tri-uoromethylated species. 9 In this context, special attention has naturally been brought to triuoromethyl-allene, 10 alkyne 11 and 1,3-diene 12 building blocks and how to access them.…”
Section: Introductionmentioning
confidence: 99%
“…[10][11][12][13] Conjugated dienes represent one group of broadly occurring and important organic compounds. Their importance stems mainly from their flexibility in organic transformations, [14][15][16][17] and the extensive amount of the 1,3-diene substructure in a vast array of natural products of biological and medicinal interest. [18][19][20][21][22][23][24][25] The development of methods for the efficient, stereoselective, and practical synthesis of conjugated dienes has attracted much interest from synthetic organic chemists.…”
Section: Introductionmentioning
confidence: 99%